The marriage and family experience intimate relationships in a changing society - Strong, Bryan; Cohen, Theodore F. (Cengage Learning, 2017)
"The Marriage & family experience offers a realistic look at relationships today, helping you see and understand the underlying issues at work in marriages, families, and all kinds of relationships. Real-life cross-cultural examples and features that encourage you to reflect on your own life and behavior make the thirteenth edition accessible and compelling. You'll find up-to-date information on adoptive parenting, childbearing patterns, gay and lesbian families, the transgender experience, the meaning of virginity, gender roles, communication and conflict resolution, the influence of popular culture, and working families. With thorough coverage that reflects the diversity of families and relationships, the book illustrates how racial, cultural, economic and sexual differences shape relationships and families, and offers a straightforward overview of the topics you must understand to succeed in your course. This is a book you can relate to and one you will want to read"--Provided by publisher.